A Detailed Review on Traditional v/s Modern Education: Navigating the Path to Learning - Dr.Vishal Kishorchandra Pandya; Vaibhavi Khilosiya; Manali Gohel (International Journal of Education Sciences, 2025)
This abstract compares traditional and modern education methodologies, analyzing their respective approaches, strengths, and weaknesses. Traditional education, characterized by face-to-face instruction, textbooks, and standardized testing, emphasizes rote learning and adherence to established curriculum. In contrast, modern education integrates technology, interactive learning tools, and personalized approaches to foster critical thinking, creativity, and adaptability. While traditional education provides a structured framework and cultural continuity, modern education addresses diverse learning styles and prepares students for the complexities of the 21st century. The abstract concludes by emphasizing the importance of recognizing the merits of both approaches and leveraging their strengths to create a balanced and effective educational system tailored to the needs of learners in a rapidly evolving world. Education has undergone a profound transformation from conventional classroom practices to technologically enhanced learning environments. This paper critically reviewed how the evolution from traditional to modern education reflects broader social, cultural, and technological shifts. Traditional education, rooted in structured learning, moral discipline, and teacher authority, has long served as the foundation for knowledge transmission. Modern education, however, introduces digital tools, collaborative learning, and adaptive pedagogies that empower learners to become active participants in their own development. The study explores how these contrasting systems influence student engagement, teacher roles, and overall learning outcomes. It argues that neither approach alone can fully meet the diverse demands of contemporary education. Instead, a hybrid model—one that combines the discipline and foundational rigor of traditional systems with the innovation and inclusivity of modern approaches—can cultivate well-rounded learners equipped for global challenges in the 21st century.
Keywords: Traditional education; classroom environment; educational technology; modern education; teacher student dynamics